Features of developmental coordination disorder in active childhood epilepsy: a population‐based study. (16th April 2015) - Reilly, Colin; Atkinson, Patricia; Das, Krishna B; Chin, Richard F; Aylett, Sarah E; Burch, Victoria; Gillberg, Christopher; Scott, Rod C; Neville, Brian G R
<x xml:space="preserve">Abstract</x> Aims To provide data on parent‐reported features of developmental coordination disorder (DCD) and describe neurobehavioural comorbidity in children with epilepsy and DCD. Method Eighty‐five (74% of those eligible) children (44 males, 41 females; age range 5–15y) with active childhood epilepsy (an epileptic seizure in the last year and/or currently taking antiepileptic drugs) in a population‐based cohort underwent comprehensive multidisciplinary assessment. The DCD Questionnaire (DCD‐Q) was completed by parents (n=69) of children with an IQ>34, of whom 56 did not have cerebral palsy (CP), and were considered for a diagnosis of DCD. Results Of those considered for a DCD diagnosis, 16 (29%) met DSM‐IV‐TR criteria whereas 34 (61%) scored in the at‐risk range on the DCD‐Q. The sensitivity of the DCD‐Q was 100% (95% CI 76–100) and specificity was 55% (95% CI 39–70). Significant predictors of higher scores on the DCD‐Q included the presence of autism spectrum disorder, CP, and early seizure onset. Increasing age and IQ were independently associated with higher DCD‐Q scores. Intellectual disability, attention‐deficit–hyperactivity disorder, academic underachievement, and specific memory problems were the most common neurobehavioural difficulties in those with both DCD and epilepsy. Interpretation Parent‐reported symptoms of DCD are very common in childhood epilepsy. The DCD‐Q has good sensitivity but lower specificity in this population.